PENERAPAN ETIKA BISNIS DALAM HUBUNGAN INDUSTRIAL PADA PRODUKTIVITAS PERUSAHAAN. - Indra Rahmat; Sabrina Putri Lestari; Anis Fitriyah; Resya Dwi Marselina; Fika Anilda; Elis Eliyanti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research is qualitative research with a descriptive approach. This research aims to explore or study the application of business ethics in industrial relations and company productivity. Research found that the application of business ethics in CV. Sugih Maju Berkah forms positive and good behavior for leaders and employees, is able to create fair relationships, and is able to protect employees from work situations that violate morality. The research results highlight that the application of business ethics not only has a positive impact on company productivity but also creates a conducive or comfortable work environment. Leaders and employees who behave ethically can build the foundation of healthy industrial relations, which in turn strengthens collaboration or unity and trust among team members. In conclusion, the application of business ethics in industrial relations at CV. Sugih Maju Berkah has a positive and excellent impact on company productivity and creates a conducive, productive and safe work environment.